PENANAMAN PROFIL PELAJAR PANCASILA DALAM MEMBANGUN KEBIASAAN HIDUP SEHAT DI SDN PANGTONGGAL 1 - Rahman, Habibur; Turasmini; Firdausi, Ghilman; Sofiyana; Sholehah, Faiqkhatus (CV. Jendela Gagasan, 2024)
This study aims to evaluate the implementation of the Pancasila Student Profile in fostering healthy living habits at SDN Pangtonggal 1, Pamekasan. The method used is descriptive qualitative, with the research population including all students and teachers at the school. Data were collected using observation instruments, structured interviews, and documentation. The results of the study show that the integration of Pancasila values, such as mutual cooperation and independence, plays an important role in increasing students' awareness of healthy living habits. Activities like Healthy Gymnastics and environmental cleanliness programs have successfully improved students' healthy habits. Active student participation in these activities reflects positive changes in their attitudes and behaviors related to healthy living habits. This study emphasizes the importance of character education and the inculcation of healthy living habits to create a healthy and competitive generation.